Exercise addiction levels of individuals exercising in fitness centers and related variables - Kayhan, Recep Fatih; Kalkavan, Arslan; Terzi, Esranur (Journal of Dependence, 2021)
Objective: The aim of this study was to determine the symptoms of exercise dependence of individuals who do sports in fitness centers and to compare them in terms of certain variables.Method: A total of 209 people, 94 men and 115 women, who regularly do sports in the fitness centers, voluntarily participated in the study. Exercise Dependence Scale-21 was applied to the athletes with the form in which personal information was questioned.Results: There was a significant difference in exercise dependence sub-dimension levels of athletes according to gender, age, income level and number of training variables. When the symptoms of the participants are examined, 96 athletes participating in the study are described as asymptomatic and 113 as symptomatic. In our study, no athlete was identified as addicted. It was found that the risk of exercise dependence was highest in men, those between the ages of 18-22, those with an income between 3001-5000 TL, and those with a low number of training.Conclusion: The athletes participating in our study were not exercise addicts but had risks, while the variables of gender, age, income and number of training could be effective in the emergence of exercise dependence symptoms. It is thought that support should be given to these athletes that a controlled, balanced and correct exercise program would be more efficient instead of excessive exercise.
Keywords: Addiction; leisure time; exercise; recreation; sport